Analysis of the Dental Caries Epidemiological Profile in Children of Benguela city, Angola - Songa, Marcial António Simão [UNESP]; Saliba, Nemre Adas [UNESP]; Saliba, Tânia Adas [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2022)
Purpose: To analyse the epidemiological profile of dental caries in children aged 5 and 12 years in the city of Ben guela, Angola. Materials and Methods: This was an observational, analytical, cross-sectional study conducted in 2019 with 190 12-year-old schoolchildren and 240 5-year-old schoolchildren from the public education system in Benguela, An gola. The relationship between dental caries and dental characteristics, sociodemographic factors, access to den tal services, oral hygiene practices, and eating habits was analysed. Dental condition was evaluated using the dmft and decayed, missing, and filled teeth (DMFT) indices. Results It was found that 62.63% (n = 119) of 12-year-old students and 42.08% (n 101) of 5-year-old students were free from dental caries. The average DMFT was 0.76 + 1.35 and dmft was 2.19 + 2.95. The majority of chil dren (56.51%) had never been to the dentist, had no dental elements restored, and none of the students used dental floss. The proportion of students who consumed sweets every day was higher at 5 years of age (46.25%) than at 12 years of age (22.63%). There was a statistically significant association (P 0.01) between the higher in cidence of dental caries and peri-urban location among 5-year-old schoolchildren. Conclusion This study showed that the prevalence of dental caries in the permanent dentition of schoolchildren in Benguela is very low; however, the situation is critical in the primary dentition, especially in the peri-urban area. The limited access to dental surgeons and lack of treatment for affected teeth highlight the need to implement and de velop public policies to promote oral health.
Keywords: Angola; Child; Dental caries; Health services accessibility